A Forest Science Effective Research Supervision in the Faculty Of Forestry, Universiti Putra Malaysia - Jusoff, Kamaruzaman (2008)
At least historically, undergraduate research supervision has predominantly been seen as part of the basic research function of academic staff. In many fields of study, success in research requires not only sophisticated experimental and analytical skills, but good mentoring and managerial skills as well. This paper presents an observational case study and perception based on the author’s true experiences exploring the most effective supervision of undergraduate students in the Faculty of Forestry, Universiti Putra Malaysia (UPM). Due to the need of a highly calibre first class honours undergraduates for the future pool of postgraduates and top notch academia in the Faculty and in UPM, the aim of this paper is therefore to provide a good practice guideline for supervision of undergraduates final year project reports/theses to ensure consistency of approach for staff and students across the faculty and university. Key topics covered include building an effective undergraduate final year project/theses supervisory relationship, negotiating expectations, providing good communication and feedback and providing motivation and guidance to them. Personal interviews of undergraduates' perceptions of their supervision as they undertake their final year research projects were presented. Students reported that only a select few of their supervisors were supportive and sympathetic to their needs. Only a few of the Faculty supervisors adopted the role of resource person, directing undergraduates to references and contacts, discussing ideas and work undertaken. Only a few students had considerable freedom in the conduct of their final year project work. They were not able to choose their own research topic and supervisor but most determined the pace at which they worked. Some appeared to cope well with the autonomous role of a junior researcher while some commented on difficulties. Though the majority of students were given considerable freedom in their research the results of the observation indicated some differences amongst supervisors.